A study of dynamic hand orthosis combined with unilateral task-oriented training in subacute stroke: A functional near-infrared spectroscopy case series - Li, ChaoJinZi; Wong, Yih; Langhammer, Birgitta; Huang, FuBiao; Du, XiaoXia; Wang, YunLei; Zhang, HaoJie; Zhang, Tong (Frontiers in Neurology, 2022)
Background: The application of fNIRS to explore brain activity under rehabilitation intervention for upper extremity after stroke is a research focus on neurorehabilitation. Objective: The purpose of this study was to explore under a grip-release ring motor task, the activated changes of regions of interest and changes of motor function utilizing fNIRS technology and test scales on persons with stroke who received unilateral task-oriented therapy with a hand orthosis in the early subacute stroke period before and after intervention. Aimed to find a sensitive motor task and region of interest first, then to evaluate the feasibility and mechanism of this rehabilitation method by utilizing fNIRS technology at the next randomized controlled trial. Methods:8 right-handed, right hemiplegia subacute stroke persons were enrolled. They received 30 minutes of unilateral task-oriented therapy without orthosis and 30 minutes with orthosis (5 days/week) for four weeks. Activated channel numbers, beta values based on oxygenated hemoglobin concentration change under a grip-release ring motor task were estimated with fNIRS. Clinical outcome measures including grip strength evaluation, action research arm test and Fugl-Meyer assessment of the arm were evaluated at the same time. Results: Individual activation analysis showed that after intervention, Subject1 2 6 7 8 had the maximum mean beta value locating in left premotor cortex, Subject 4 5 had the maximum mean beta value locating in left sensorimotor cortex. The activation analysis of Subject 3 showed the maximum mean beta value locating in right premotor cortex. Deactivations of left sensorimotor cortex, left premotor cortex, bilateral prefrontal cortex were observed after intervention.Group activation analysis showed that bilateral cerebral hemispheres were activated, right hemisphere and right supplementary motor cortex were activated dominantly. After the intervention, the activation of bilateral hemispheres decreased . Each participant demonstrated improvements in all the clinical test scales after intervention. Conclusions: Left premotor cortex, left sensorimotor cortex and right supplementary motor cortex may be the primary region of interest. Grasp-release ring task was not appropriate to achieve our fNIRS research objective and more sensitive motor task or more sensitive evaluating indicator should be searched in further studies.